Evaluation of Antarctic strains of Bacillus sp. as plant growth promoting bacteria - Zambrano-Solórzano, Ángela; Guzmán-Cedeño, Ángel; Pincay, María; Chicaiza, Jonathan; Zambrano, Diego (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
In agriculture, efficient microorganisms are used, among them plant growth-promoting bacteria. This work aimed to determine, in vitro, the mechanism of action in strains of Bacillus sp. isolated from Antarctica. The analyzed characteristics of the bacterium were: catalase and hemolysis tests, Gram stain, phosphate solubilization, growth without a nitrogen source, siderophore production, and survival at different values of pH, NaCl, and temperature, which confirmed the ecological plasticity and adaptation of these strains in environments other than their origin. According to the desirable characteristics, the T5, GB-70, and B-6 strains were chosen and added to two substrates: clay and clay-compost mixture, which were sterilized and placed in 200 mL glass bottles, and a corn seed was planted in each of them. After two weeks, the following parameters were evaluated: length of root (LR), seedling height (AP), and shoot diameter (DT). The simple effect of the strains as independent variables and their interaction did not significantly affect the response variables evaluated, recording the following averages: 12.84 cm (LR), 15.28 cm (AP), and 2.26 cm (DT). Considering the substrate, the compost + clay significantly (p<0.05) influenced the LR and DT characteristics of the seedlings, with averages of 14.44 and 2.38 cm, respectively. The observed mechanisms of action distinguish promising strains that could be validated at the field level in agricultural production systems when inoculated in organic fertilizers.